Adapting Strategies to Maintain Efficiency During a Cull of Yellow-Legged Gulls - Sugoto Roy; Ray Ridley; Jeff Sandon; John R. Allan; Peter S. Robertson; Andrew Baxter (Human-Wildlife Interactions, 2017)
Increasing populations of yellow-legged gulls (Larus michahellis) in the Mediterranean have created conflicts with seabird conservation, migrating raptors, and humans. As a mitigation measure, gulls are routinely culled in the region. Previous studies of extended culls show that catch per unit effort declines over time through a combination of population reductions and avoidance behaviors developing within the remaining population. We countered these problems during a 4-year cull of yellow-legged gulls in Gibraltar by matching the type and mode of deployment of firearms in response to changes in gull distribution and behavior. We found that shotguns were effective when gulls mobbed operators near nesting areas, while rifles were more effective as gulls became wary and retreated farther from the operators. Changing the type of firearm enabled us to counter the expected rate of decline in culling efficiency throughout the project. We were most efficient in the first year of the project, killing gulls at a mean rate of 8.35 birds per man-hour. Although this declined to 4.83 by the third year, the adjustments that we made to the way firearms were deployed raised it to 6.4 in the fourth year despite a 79% decline in the observed total gull population over this period. We modelled the population data collected using a Leslie Matrix to evaluate the impact of management at the end of the culling period. The population declined at a greater rate than explained by the numbers actually culled, suggesting that the cull resulted in an additional disturbance, which triggered emigration at a rate of 35%, over and above the numbers culled.